Effects of Variations in the Application of Cocoa Pod Shell Compost and Mexican Lilac Liquid Organic Fertilizer on the Growth and Production of Yellow Bell Pepper Plants in Lowland - Hairuddin, Rahman; Muhajir, M.; Hamdani, Ulfah Zakiyah (Agrotech Journal, 2023)
A research study aimed at evaluating the efficacy and determining the optimal dosage of cocoa pod shell compost fertilizer for enhancing the growth and production of yellow pepper plants in the lowland was conducted. This research was carried out at Experimental Field II, Faculty of Agriculture, Cokraminoto University, Palopo, located on Jalan Lamaranginang, Batu Pasi Village, North Wara District, Palopo City, from July to October 2023. The experimental design employed was Randomized Block Design, encompassing six treatments with four replications. The level treatments used were designed as follows: P0 (no treatment), P1 (135 gr cocoa husk compost and 100 ml/L of liquid organic fertilizer of mexican lilac), P2 (185 gr cocoa husk compost and 150 ml/L of liquid organic fertilizer of mexican lilac), P3 (235 gr cocoa husk compost and 150 ml/L of liquid organic fertilizer of mexican lilac + 200 ml/L of liquid organic fertilizer (gamal), P4 (cocoa pod husk compost 285 gr and liquid organic fertilizer of mexican lilac 250 ml/L, P5 (cocoa pod husk compost 335 gr and liquid organic fertilizer of mexican lilac 300 ml/L).Â  The parameters observed included plant height, flowering age, number of flowers, number of fruit, fruit weight and fruit diameter. Upon conducting research and data analysis, it was revealed that the P3 treatment exerted a highly significant effect on the parameters of fruit weight (449.78 grams).Â  Conversely, P3 demonstrated no significant impact on the parameters of the number of fruits (4.00), fruit diameter (135.20 cm), plant height (39.38 cm), number of flowers (7.88 florets) and flowering age (34.63 HST). In light of these findings, it is recommended to consider an increase in the dosage of cocoa pod husk compost and liquid organic fertilizer (Mexican lilac) to optimize the growth and production of yellow bell pepper plants in subsequent research endeavors